On the issue of the place of dialect phraseology in the ethnocultural space of Austria - Andreevich Chukshis, Vadim (2021)
The multidimensional study problem of Austrian dialect phraseology continues to be relevant and of scientific significance. This article aims to cover not only purely linguistic questions from the phraseological corpus of the Austrian dialect, but also to study the phraseological units of the Austrian dialect as a brilliant means of expressing two Austrian ethnic culture.